An Economic Assessment of Woodlots for Smallholder Farms in the Coast Region of Kenya. Issue 1 (5th July 2019) - Wekesa, Linus; Mwalewa, Sylivia; Muema, Kevin; Muthini, Joseph; Riziki, Phedister; Mukirae, Peter; Menya, Carolyne
ABSTRACT: Little is known about economic viability of woodlots being integrated in smallholder production systems in the Coast Region of Kenya. The current study was therefore conducted as a cross-sectional survey covering a sample size of 282 smallholder farmers in the Coast Region to generate information on economics of woodlots. Farmers were sampled using stratified random sampling procedures and a questionnaire with open and closed ended questions was applied to collect growth data, costs of production and benefits. We investigated the economics of woodlots on smallholder farms by estimating the nett present value and annual equivalent values of various woodlot enterprise opportunities. Results show that Casuarina equisetifolia is the most profitable woodlot enterprise. Production of C. equisetifolia is economically viable and has better financial returns than any other woodlot enterprise. Profitability of woodlots on smallholdings depends on level of integration into existing farming systems, market outlets where products are sold and level of value addition. Highest profitability is achieved when woodlots are intercropped with maize at initial stages of establishment, and selling their processed products through local market centres; one acre of C. equisetifolia gives an average nett present value of KES 856 117, which translates to a discounted annual profit margin of KES 153 361 over a seven-year rotation period. The Melia volkensii and Gmelina arborea woodlots are equally profitable with average nett present values of KES 583 486 and KES 514 301, respectively leading to conclusion that woodlots are economically viable on smallholdings in the Coast Region. It was accordingly recommended that smallholder farmers in the Coast Region be encouraged to integrate woodlots of high value trees in their farming systems to help diversify and optimise their farm incomes.